Vowel representations in the invented spellings of Spanish-English bilingual kindergartners - Raynolds, Laura B.; Uhry, Joanna K.; Brunner, Jessica (Reading and Writing, 2013)
The study compared the invented spelling of vowels in kindergarten native Spanish speaking children with that of English monolinguals. It examined whether, after receiving phonics instruction for short vowels, the spelling of native Spanish-speaking kindergartners would contain phonological errors that were influenced by their first language. Results showed no differences between the two groups on the number of correct short vowel spellings, even though the sounds for four of the five English short vowels do not exist in Spanish. By contrast, differences were observed in the representation of long vowels with a higher rate of error among ELLs. The students had not received explicit instruction in long vowels. ELLs appeared to be trying to represent the diphthongized nature of some English long vowels by spelling long vowels with more than one vowel. The results support the authors' hypothesis that kindergarten phonics instruction had an impact on the invented spellings of new second language vowel phonemes.
Keywords: Bilingual; English language instruction; Invented spelling; Spanish language; dept.cur; peer-reviewed